A Comparative Analysis of the Function of Declensional Meanings - Haroutyunyan, Zaven (Armenian Folia Anglistika, 2008)
Language-speech transformation proves essential for the existence and functioning of any language system. Language was born to meet various needs of the public, namely to make verbal communication possible. The article specifies the general observation of the fundamental function of the language with linguo-philosophical investigation of the role of declensions. The research aims not only to clarify the grammatical links or the description of the syntactic and morphological functions of the declensions in a sentence, but rather their semantic analysis. The problem of declensions not only refers to language-speech mutual transformation, but gives an opportunity to observe the peculiarities of the latter. This idea is confirmed when we compare the declension system of the Armenian language (synthetic language) with the declensions of the same nature in French (analytical language). Speech realization probably calls for the presence of certain syntactic structures. The declensional system as a potential source of such structures acts as a sort of “skeleton” in the process of language – speech transformation.